Impacts on Canadian agriculture of the Convention on Biological Diversity - Harvey, Bryan L.; Fraleigh, Brad (Canadian Journal of Plant Science, 1995)
Canada was among the first nations to sign and ratify the Convention on Biological Diversity. With strong support from the federal government, the Canadian delegation played a key role in its negotiation. The Convention has three major elements: (1) the conservation of biodiversity; (2) the sustainable use of biodiversity; and (3) the equitable sharing of benefits derived from the use of biodiversity. Canada has developed a draft strategy to meet our obligations as a signatory nation. This strategy was developed with input from various levels of government and from a wide range of individuals and organizations. The benefits to agriculture are increased resources for the conservation of biodiversity, which is vital to this industry, and continued access to germplasm. The costs are the funds necessary to conserve, an obligation to share knowledge and benefits from genetic resources and greater regulation of germplasm exchange. Key words: Biodiversity, conservation, germplasm, convention, genetic resources